As-Shuwar as-Salbiyyah li al-Mar’ah fî Amtsâl al-‘Arabiyyah wa al-Amtsâl as-Sawâhiliyyah (Dirâsah Muqâranah) - Faisal Masuod Muhindo (Jurnal Internasional Pendidikan Bahasa Arab, 2022)
This study aimed to reveal the image of women in Arabic and Swahili Proverbs, and to identify the issues and meanings addressed by the owners of the environment in which the proverbs were said and broadcasted, in addition to highlighting the sweetness felt in the proverbs of humor and anagrams, which enhances literary pleasure. The research methodology used for this study was the comparative approach whereby an image of women was presented through Arabic and Swahili proverbs, and the researcher also used the descriptive analytical approach to highlight the contents of proverbs and their significance to reveal the image of women that reflects their status in society, and this enabled the researcher in comparing the image of omen between Arabic and Swahili proverbs. The results of the research indicated that there are proverbs in Arabic and Swahili languages that glorifies women and raises their status which are few when compared to other proverbs that detract their status and reduce their value, we sometimes find that the two extremes coexist in one example.